The Contribution of Intercultural Psychology to Clinical and Research Projective Assessment Approaches - Costa-Fernandez, Elaine; Guerraoui, Zohra; Sturm, Gesine; Reveyrand-Coulon, Odile (Journal of Organizational Psychology, 2021)
This article discusses the contribution of intercultural psychology to projective evaluation methods in clinical intervention and research. It is part of the intercultural psychology field which supports, at the epistemological level, the intimate constitutive relationship between the contexts of belonging and the always unique development of the psychological subject. In order to understand the specificities and the stakes of this perspective on the projective clinic, we will first analyze the foundations of intercultural psychology, then address the complexity of cultural belonging in the contemporary world, and finally open up new perspectives of projective evaluation both in clinical practice and in research situations.